Factors Associated with the Development of Skin Lesions in Hospitalized Patients Admitted to a Nursing Preventive Care Program in Colombia - Escobar, Gaby E.; Espinosa, Ángela F.; Cortés, Olga L.; Molano González, Nicolás (Investigación y Educación en Enfermería, 2025)
Objective. This work sought to determine the factors associated with the development of skin lesions among patients hospitalized and admitted to a preventive skin care program carried out by nursing. Methods. Analytical observational study of cases and controls, which included a sample of 150 cases and 300 controls hospitalized in a clinic with tier IV level of complexity in Bogotá (Colombia). A classification and regression tree was developed to explore the complex interactions that define cases and controls. Results. According to the decision tree, the factors that represent greater probability for the development of skin lesions in the study population were the preventive use of hydrocolloid dressings, hospital stay > 12 days, BMI > 23, incontinence, diagnosis upon admission related with cardiovascular problems and peripheral vascular disease, cancer, surgery, or respiratory failure. Conclusion. Development of skin lesions was related with the interaction of different clinical conditions presented by the patients. Integration of this knowledge is essential for structuring preventive care programs in high-complexity hospitals and in formulating individualized care plans.